Fracture research from India between 1989 to 2022: A scientometric study - Vaishya, Raju; Gupta, Brij Mohan; Kappi, Mallikarjun; Vaish , Abhishek (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. Research on fractures has increased rapidly in India in recent years, but no bibliometric study has been performed on this subject. From the Scopus database, we aimed to examine the bibliometric characteristics, trends, and current status of India’s fracture research and publications between 1989 and 2022. Design/Methodology/Approach. We identified the key organizations, authors, journals, and important keywords, besides studying and visualizing their collaborative interactions using VOSviewer and Biblioshyn software. Results/Discussion. The 1046 India fractures research publications were identified and cited 8927 times. External funding was received by 1.91%, and 11.95% had international collaboration. The 894 authors from 304 organizations and publishing in 88 journals were involved in India’s fracture research. The most productive organization was AIIMS, New Delhi. The most impactful organization was JIPMER, Pondicherry; the most productive author was V. Trikha. The most productive journal was the Indian Journal of Orthopaedics (n=257), and the most impactful journal was Acta Orthopaedica. Femur was the top anatomical location studied for fracture research, followed by Humerus and Tibia. Hip fractures were the most emphasized fracture research areas in older people, in contrast to Humerus, and Femur fracture research in adolescents and children. Delhi was the epicentre of research. Conclusion. This study is the first comprehensive bibliometric analysis of India’s fracture research over 30 years. It provided an insight into its current and past research status and hopes to guide scholars to understand research frontiers and directions in fracture-related research.